Futsal and Values of Togetherness: Building Sportsmanship in the Young Competition DAAI TV Medan - Honkley, Tony; Diana; David; Lina; Robinson (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The Futsal Young Competition organized by DAAI TV Medan aims to enhance the spirit of sportsmanship and teamwork among youth. This event focuses not only on sports skills but also on the development of positive values such as cooperation, discipline, and healthy competition. Through this futsal tournament, participants are given the opportunity to improve their athletic abilities while strengthening their teamwork skills. The methods employed in this community service initiative include intensive training, team matches, and group discussions on the importance of sportsmanship and ethics in competition. The expected outcome of this activity is the creation of a more sportive environment among the youth, as well as fostering stronger bonds of brotherhood among young people from various backgrounds. Thus, this competition plays a crucial role in shaping youth who are not only excelling in sports but also exhibiting collaborative and positive attitudes in daily life.